Relationship of Locus of Control with Middle School Student Discipline - Nadyya Nulhusni; Marjohan Marjohan (Jurnal Neo Konseling, 2019)
School discipline is very important to implement because it can provide support for the creation of behavior that is not deviant, encourage students to do good and right, help students understand and adapt to the demands of their environment and stay away from doing things that are prohibited by the school, students learn to live with habits - good and beneficial habits for him and his environment. However, the reality in the field found many students who violated the rules that had been made by the school. For this reason the aim of this research is to describe student discipline, locus of control, and how the relationship between locus of control and student discipline.This type of research is descriptive correlational which aims to find facts in accordance with the actual situation. The research subjects were 100 class VIII and IX students at SMP Negeri 13 Padang. The instrument of data collection is the student disciplinary questionnaire that uses a Likert scale and inventory locus of control that uses standard techniques that have been adopted from Dr. Marjohan M.Pd., Kons. Data was processed using descriptive statistical analysis techniques and to test the relationship of data was analyzed using the Pearson Product Moment formula with the Statical Product and Service Solution (SPSS) program version 20.0. The results of this study reveal that: (1) locus of control has an internal locus of control tendency, (2) Discipline of students is in the medium category, (3) there is a significant negative relationship between locus of control and student discipline in SMP Negeri 13 Padang with a significant value of 0.045. Based on the findings of this study, it is expected that BK teachers or counselors can provide assistance in the form of Counseling Guidance services.